2014
DOI: 10.1016/j.taap.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential role of tungsten carbide cobalt (WC-Co) nanoparticle internalization in observed toxicity toward lung epithelial cells in vitro

Abstract: Tungsten carbide cobalt (WC-Co) has been recognized as a workplace inhalation hazard in the manufacturing, mining and drilling industries by the National Institute of Occupational Safety and Health. Exposure to WC-Co is known to cause “hard metal lung disease” but the relationship between exposure, toxicity and development of disease remain poorly understood. To better understand this relationship, the present study examined the role of WC-Co particle size and internalization on toxicity using lung epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 76 publications
(99 reference statements)
8
38
2
Order By: Relevance
“…75 In addition, nano-WC-Co has been found to induce greater cellular toxicity and higher levels of oxidative stress than micro-WC-Co particles of the same composition under identical conditions (Figure 2). 86 These studies are consistent with the other reports where the Toxicity of nano-wC-Co was cell dependent, macrophages in the co-culture may play a protective role against nano-wCCo-mediated toxicity, and nano-wC-Co exposure stimulated the M1 phenotype of macrophages 87…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognsupporting
confidence: 92%
See 1 more Smart Citation
“…75 In addition, nano-WC-Co has been found to induce greater cellular toxicity and higher levels of oxidative stress than micro-WC-Co particles of the same composition under identical conditions (Figure 2). 86 These studies are consistent with the other reports where the Toxicity of nano-wC-Co was cell dependent, macrophages in the co-culture may play a protective role against nano-wCCo-mediated toxicity, and nano-wC-Co exposure stimulated the M1 phenotype of macrophages 87…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognsupporting
confidence: 92%
“…Early data concerning the effects of inhaled WC-Co dusts first emerged in the 1960s and continued through the 1980s, providing researchers the foundation to further explore the toxic effects of hard metal exposure using in vitro [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] and in vivo 72,[89][90][91][92][93][94][95][96] models. Although cobalt itself was originally considered the causative agent of HMLD, several studies demonstrated that this is not the case and the disease mainly develops due to the simultaneous presence of WC with Co. 71,74,[76][77][78][79]90,91 It is currently understood that the combination of WC-Co is more toxic than Co, W, or WC particles alone, both in vitro and in vivo, 71,72,74,78,79,81,85,90,91,93,94,…”
Section: Risk Of Wc-co Exposure: Hard Metal Lung Disease (Hmld) Prognmentioning
confidence: 99%
“…The presence of WC-Co particles did not interfere with the MTT assays in our studies as we described earlier. 49 Macrophage polarization assay THP-1 cells were seeded at a density of 5×10 5 cells/mL in RPMI-1640 containing 10 ng/mL PMA in a 12-well culture dish and incubated for 48 h to stimulate M0 cell differentiation. Media were then aspirated from each well and replaced with DMEM containing 100 ng/mL LPS (M1 stimulus/ positive control), 20 ng/mL IL-4 (M2 stimulus/positive control) and 0, 1, 10 or 100 μg/mL nano-WC-Co particles.…”
Section: Cell Viability After Nano-wc-co Exposurementioning
confidence: 99%
“…49 Briefly, nano-WC-Co particles averaged 98 nm in diameter in suspension determined by dynamic light scattering and transmission electron microscopy. Compositional analysis by energy-dispersive X-ray (EDX) determined that nano-WC-Co contained 72.13% tungsten, 13.42% cobalt, 7.63% carbon and 6.81% oxygen.…”
Section: Nano-wc-co Characterizationmentioning
confidence: 99%
See 1 more Smart Citation